2009
DOI: 10.1002/ijc.24269
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism for anti‐EGFR antibody action involves chemokine‐mediated leukocyte infiltration

Abstract: Overexpression of the epidermal growth factor receptor (EGFR) is a hallmark of squamous cell carcinoma of the head and neck (SCCHN). Monoclonal antibodies (mAbs) against EGFR are currently used for therapy of recurrent or metastatic disease; however, their mode of action is not completely understood. To investigate the immunological effects of anti-EGFR mAb, we generated a three-dimensional spheroid model of EGFR-expressing SCCHN and used this model to study the effect of anti-EGFR mAb on leukocyte migration t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 45 publications
(66 reference statements)
5
37
0
Order By: Relevance
“…Furthermore, stromal cells have been incorporated into MCTS models using different configurations. Tumor cells have been mixed with stromal fibroblasts prior to spheroid formation [131,132]; spheroids have been placed on fibroblast monolayers [133]; fibroblast spheroids have been added to MCTS [134,135]; MCTS have been added to a fibroblast suspension; and fibroblast spheroids have been added to MCTS [73]. Melanoma MCTS have also been combined with endothelial cells to evaluate the potential role of angiogenesis in cancer progression [136], and melanoma MCTS have been incorporated into engineered skin models to evaluate combinatorial treatment regimens [137].…”
Section: Spheroid Co-culturementioning
confidence: 99%
“…Furthermore, stromal cells have been incorporated into MCTS models using different configurations. Tumor cells have been mixed with stromal fibroblasts prior to spheroid formation [131,132]; spheroids have been placed on fibroblast monolayers [133]; fibroblast spheroids have been added to MCTS [134,135]; MCTS have been added to a fibroblast suspension; and fibroblast spheroids have been added to MCTS [73]. Melanoma MCTS have also been combined with endothelial cells to evaluate the potential role of angiogenesis in cancer progression [136], and melanoma MCTS have been incorporated into engineered skin models to evaluate combinatorial treatment regimens [137].…”
Section: Spheroid Co-culturementioning
confidence: 99%
“…It is important to note that immune response can be stimulated by promoting infiltration and cytotoxicity of leukocytes in MCTS. 51 For example, it was demonstrated that the blocking of lactic acid secreted by tumor cells increased the migration of monocytes into MCTS. …”
mentioning
confidence: 99%
“…Each of the cells represents a potential target for decoding the clinical heterogeneity of CLM patients, for developing new biomarkers, and consequently for developing new personalized immunotherapies. In line with this, some experimental data showed that the blocking of the EGFR pathway was associated with an increased immune infiltration in solid cancers (90,91). In this regard, several in vitro and in vivo models have shown that the masking of EGFR with a specific blocking monoclonal Ab (mAb) inhibits tumor proliferation, induces terminal cellular differentiation and modulates chemo-and radio-sensitivity (92).…”
Section: The Role Of the Host Immune Systemmentioning
confidence: 80%
“…In this regard, several in vitro and in vivo models have shown that the masking of EGFR with a specific blocking monoclonal Ab (mAb) inhibits tumor proliferation, induces terminal cellular differentiation and modulates chemo-and radio-sensitivity (92). Recently, it has been also reported that the inhibition of the EGFR signaling pathway facilitates the activation of immune cells and their recruitment to tumor sites via the production of several cytokines and chemokines (90). This is particularly relevant for NK cells, as studies have shown that the use of a blocking anti-EGFR mAb stimulates these innate immune effector lymphocytes and induces antibodydependent cell cytotoxicity (93,94).…”
Section: The Role Of the Host Immune Systemmentioning
confidence: 99%